2018
DOI: 10.3390/ma11040545
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance and Polarization Corrosion Studies of Tantalum Surface Modified by DC Plasma Electrolytic Oxidation

Abstract: Tantalum has recently become an actively researched biomaterial for the bone reconstruction applications because of its excellent corrosion resistance and successful clinical records. However, a bare Ta surface is not capable of directly bonding to the bone upon implantation and requires some method of bioactivation. In this study, this was realized by direct current (DC) plasma electrolytic oxidation (PEO). Susceptibility to corrosion is a major factor determining the service-life of an implant. Therefore, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
5
23
0
Order By: Relevance
“…Generally, it was higher in the electrolytes having higher ionic strength. Similar observations were noted for the PEO of Ta in the comparable electrolytes [ 57 ]. However, it was found that the addition of magnesium acetate to the first solution led to the higher rates of voltage increase than those that were observed after the addition of calcium formate (14.1 and 16.0 V/s, respectively).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Generally, it was higher in the electrolytes having higher ionic strength. Similar observations were noted for the PEO of Ta in the comparable electrolytes [ 57 ]. However, it was found that the addition of magnesium acetate to the first solution led to the higher rates of voltage increase than those that were observed after the addition of calcium formate (14.1 and 16.0 V/s, respectively).…”
Section: Resultssupporting
confidence: 87%
“…The authors of the research have already conducted some studies on DC PEO of zirconium in silicate solutions [ 54 , 55 ]. This paper is a continuation of the two previous reports concerning PEO of niobium [ 56 ] and tantalum [ 57 ] that were carried out in the electrolytes that contained calcium hypophosphite, calcium formate, and magnesium acetate. Ha et al [ 46 ] also treated Zr under DC conditions in the presence of Mg(CH 3 COO) 2 , however, their investigations were limited to the surface characterization of the coatings, and their subsequent chemical modification in H 2 SO 4 and NaOH.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations